Challenges and critical success factor of P2P lending for SMEs in Malang - Novi Primita Sari; Zainal Arifin (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
The development of digital business and telecommunications has become increasingly rapid, in the last 10 years. The use of digital technology, which is growing rapidly, has also changed the perspective of society as a whole in interacting socially and has even fundamentally changed the industrial sector, especially the banking and financial industry. The presence of financial technology, where the financing process is carried out using digital economic tools known as P2PL (Peer to Peer Lending). The existence of this financing service product is believed to be able to provide a solution to increase the financial inclusion index. Based on these conditions, researchers are very interested in researching and revealing what are the challenges and tips for successful financing processes for SMEs. From the results of this study, it has a contribution to stakeholders in the future related to making decisions on P2PL financing products in particular so that they are better known to the public and successful in their distribution.